The Integrating Islamic Values into Quality Culture: A Case Study of Educational Practices at Madrasah Ibtidaiyah Al Mujahidin Samarinda - Tiara Puspa Tsurayya; Siti Julaiha (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
Quality education in Indonesia continues to face various challenges amid rapid digital development, where schools are required not only to improve academic performance but also to strengthen character education based on Islamic values. This article focuses on the implementation of quality culture in Islamic education at MI Al Mujahidin Samarinda. The purpose of this study is to identify the quality values applied in the madrasah and to describe how these values are implemented in daily educational practices. This research uses a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation involving the head of the madrasah, teachers, and students. The data were analyzed descriptively through data reduction, data display, and conclusion drawing, with source and method triangulation to ensure validity. The findings show that quality culture at MI Al Mujahidin Samarinda is reflected in daily practices such as Qur’an memorization (tahfiz), congregational Duha prayer, regular religious gatherings, and the habit of greeting teachers, which emphasize religious values. In addition, discipline, responsibility, professionalism, and ihsan are also consistently applied through school routines and teacher development activities. The implementation of quality culture is carried out through structured stages including planning, implementation, monitoring, and evaluation. Overall, quality culture at MI Al Mujahidin Samarinda is not limited to academic achievement, but is deeply integrated into the formation of students’ character based on Islamic values. These findings provide practical insights for other Islamic educational institutions seeking to strengthen quality management through the integration of Islamic values, thereby contributing to the broader improvement of madrasah education quality. Keywords: Case Study, Character Education, Culture of Quality, Islamic Education, Madrasah.